Propuesta para la planificación y control operacional según los requisitos de la NTC ISO 9001:2015 de una empresa dedicada a la fabricación de ojos para muñecos y artículos plásticos (2018)
Industrias Pelufa is an organization dedicated to the manufacture of eyes for dolls and plastic articles, with a great trajectory in the market, since it has more than forty years of history. Despite this, the organization has been presenting problems of non-conformities in its products during the last seven months. This monograph is based on the identification of problems or failures that have led to non-conformities, to then make a proposal based on chapter eight of the NTC ISO 9001: 2015, which improves these problems and therefore reduce non-conformities.